Foxd1 is required for terminal differentiation of anterior hypothalamic neuronal subtypes - Newman, Elizabeth A. (Dev Biol, 2018)
Although the hypothalamus functions as a master homeostat for many behaviors, little is known about the transcriptional networks that control its development. To investigate this question, we analyzed mice deficient for the Forkhead domain transcription factor Foxd1. Foxd1 is selectively expressed in neuroepithelial cells of the prethalamus and hypothalamus prior to the onset of neurogenesis, and is later restricted to neural progenitors of the prethalamus and anterior hypothalamus. During early stages of neurogenesis, we observed that Foxd1-deficient mice showed reduced expression of Six3 and Vax1 in anterior hypothalamus, but overall patterning of the prethalamus and hypothalamus is unaffected. After neurogenesis is complete, however, a progressive reduction and eventual loss of expression of molecular markers of the suprachiasmatic, paraventricular and periventricular hypothalamic is observed. These findings demonstrate that Foxd1 acts in hypothalamic progenitors to allow sustained expression of a subset of genes selectively expressed in mature neurons of the anterior hypothalamus.